Economic crises in the thirties and today - Christoph Buchheim (Intereconomics, 2009)
In the context of the ongoing financial and economic crisis reference is frequently made to the Great Depression of the 1930s and fears are voiced that we may have embarked on a similar path. This article looks at the conditions prevailing back then and compares them with the present economic environment. From this some conclusions are drawn as to the likelihood of a recurrence of the disaster.
Keywords: 330